Patterns Of Interpersonal Communication Of Otherwise Children And Parents In Maintaining Relationship (Case Study Of Fis Students At The State Islamic University Of North Sumatra) - Amri, Khairul; Abidin, Syahrul; Faishal, Muhammad (International Journal of Cultural and Social Science, 2022)
This research is entitled "Patterns of Interpersonal Communication of Overseas Children and Parents in Maintaining Silaturahmi (Case Study of FIS UIN North Sumatra Students)" with the aim of knowing how the patterns of interpersonal communication of overseas children and parents of students of the Faculty of Social Sciences, State Islamic University of North Sumatra in maintaining friendship. Communication carried out by overseas children and parents of FIS UIN North Sumatra students experience long-distance relationships with differences, communication between overseas children and parents uses media as a communication unit when they live far apart. Then the research method used for this research is field research. The nature of this research is qualitative descriptive with the aim of analyzing the problem based on interpersonal communication patterns of overseas children and parents in maintaining friendship at FIS UIN North Sumatra. The technique of collecting data in this study used by the author is interviews, observation, and documentation. The results of this study are obtained if the communication patterns used by students of the Faculty of Social Sciences, State Islamic University of North Sumatra and their parents are Media Communication Patterns, Consensual Communication Patterns, and Laissez Faire Communication Patterns. It is evident from interviews with 12 people in this study using the pattern. Media Communications because they establish long-distance relationships so that they use the media to establish communication, among the 12 informants in this study there were 8 people using the Consensual Communication Pattern, namely making a harmonious relationship and having openness with fellow individuals in communicating because of frequent communication between overseas children and parents almost every day.